Potential resources recovery opportunities from wastewater: a review - Tran Thi Kim Anh (Journal of Technical Education Science, 2018)
Nowadays, two important issues to achieve sustainable development which need to be urgently considered are water scarcity and natural resource depletion. According to UN 2006, around 700 million people in 43 countries suffer today from water scarcity. Besides, due to the population growth, natural non-renewable resources are forecasted to be depleted in the coming years. Therefore, wastewater is now recognized not only as a needed treated resource but also as a “renewable” resource, in which valuable components can be recovered. A number of technologies have been recently investigated to achieve the objective of valuable resources recovery from wastewater in order to reduce water scarcity, resource depletion, preserve the environment and reduce the cost of wastewater treatment. This paper reviews treatment methods for water reclamation, acid/base regeneration from wastewater and phosphorous recovery from municipal wastewater to achieve sustainable development. The treatment options are discussed and novel treatment processes are proposed based on a literature review.